Nontraditional security challenges in South Asia - Bhuiya, Abbas; Chakrabarti, P.G. Dhar; Jayawardane, Amal; Joseph, Mallika; Karim, Mahin; Khatri, Sridhar K.; Pirages, Li Li, Dennis; Tauqeer, Ali; Sobhan, Farooq; Upreti, Bishnu Raj; Sheikh, Stacy D. VanDeveer (© 2012 by The National Bureau of Asian Research, 2016)
This book was published by National Bureau of Asian Research [ © 2012 by The National Bureau of Asian Research] and the definite version is available at: https://muse.jhu.edu/book/21888